The Effect Of Perceived Organizational Support And Compensation On Turnover Intention With Job Satisfaction As A Mediating Variable (Study on Gen Z Employees at PT XYZ) - Siti Fatimah, Dyah Ayu; Kasmawati, Yuni (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
In today's work world, generation Z has the largest population compared to previous generations. Generation Z tends to pursue what they want so they often change jobs. Therefore, companies need to manage so that Gen Z employees do not have the desire to leave the company. Therefore, this study aims to analyze the Influence of Perceived Organizational Support and compensation on turnover intention with job satisfaction as a mediating variable. The study was conducted at PT. XYZ with a sample of 180 Gen Z employees. The sampling technique was probability sampling, while data collection used a questionnaire and data analysis techniques used SEM (Structural Equation Model) with the SmartPLS (Partial Least Square) approach. The results showed that perceived organizational support had a negative and significant effect on turnover intention. Compensation had a negative and significant effect on turnover intention. Job satisfaction had a negative and significant effect on turnover intention. Perceived organizational support and compensation had a positive and significant effect on job satisfaction. The role of job satisfaction as a mediator of the influence of perceived organizational support on turnover intention was proven to have a negative and significant effect. Likewise, job satisfaction was proven to mediate the influence of compensation on turnover intention, which was proven to have a negative and significant effect.